Analisa Kerusakan Komponen dan Interval Waktu Perawatan Unit Mobil Avanza (Studi Kasus: PT. XYZ Surabaya) - Mujianto, Slamet; Sajiyo, Sajiyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to enhance the reliability of PT. XYZ Surabaya's rental fleet, which experienced numerous incidents of damage to Avanza units from 2019 to 2023. The Westinghouse analysis method was employed to determine repair intervals and calculate the Mean Time to Failure (MTTF) for component replacements. The findings revealed that the oil filter and clutch assy components were the most frequently damaged. The oil filter requires replacement every 1460 hours (60 days) with a reliability of 52.31%, while the clutch assy needs replacement every 3429 hours (142 days) with a reliability of 46.78%. The performance of mechanics in replacing these components was also analyzed to improve efficiency. This study assists PT. XYZ in minimizing downtime, extending component lifespan, and enhancing operational efficiency, ultimately contributing to customer satisfaction and the sustainability of the vehicle rental business.